Experimental, Acquisitional and Corpus Linguistic Approaches to the Study of Morphonotactics (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
This volume presents results of bilateral research project BeSyMPHONic (ÖAW/Univ. Toulouse) funded by ANR & FWF. Differences between the two languages with respect to the processing of morphonotactic (MPH) vs. phonotactic (PH) consonant clusters are shown for the first time, the linguistically challenging claim that differences between MPH and PH are also realized phonetically is refuted, and the importance of the relative morphological richness of a language is illustrated.